ANALISIS KECERDASAN EKOLOGIS SISWA SEKOLAH DASAR DI SD NEGERI 147 PEKANBARU (STUDI DI KELAS TINGGI SD NEGERI 147 PEKANBARU) - Tri Rusmiyati; Eddy Noviana; Zufriady (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2019)
Ecological intelligence is an ability or competence possessed by individuals to adapt to their surrounding environment and apply it in daily life. In this study, the researchers examined the ecological intelligence of upper-grade elementary school students in terms of skills. Ecological intelligence in the skill dimension includes skills in using and utilizing resources, living in harmony with environmental conservation, solving environmental problems, and demonstrating responsibility toward the environment. This study employed a descriptive quantitative research design. The primary data were obtained through questionnaires distributed to respondents, while secondary data were collected through interviews and documentation as supporting data. The results of this study indicated that the ecological intelligence of upper-grade elementary school students was categorized as skilled, with a percentage of 89.89%. When viewed from each indicator, the ecological intelligence of upper-grade elementary school students was also categorized as skilled. These findings indicate that upper-grade elementary school students have begun to understand the importance of environmental protection and have shown concern for their surrounding environment.